2011
DOI: 10.1038/ejhg.2011.40
|View full text |Cite
|
Sign up to set email alerts
|

The genetic component of human longevity: analysis of the survival advantage of parents and siblings of Italian nonagenarians

Abstract: Many epidemiological studies have shown that parents, siblings and offspring of long-lived subjects have a significant survival advantage when compared with the general population. However, how much of this reported advantage is due to common genetic factors or to a shared environment remains to be resolved.We reconstructed 202 families of nonagenarians from a population of southern Italy. To estimate the familiarity of human longevity, we compared survival data of parents and siblings of long-lived subjects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…This observation could indicate that the impact of genetic effect becomes more gender-specific during advanced age than at younger ages, and that the genetic effect in old age might be most pronounced for males. Such a difference between genders was recently suggested by Montesanto et al for Italians (Montesanto et al (2011)). …”
Section: Discussionsupporting
confidence: 60%
“…This observation could indicate that the impact of genetic effect becomes more gender-specific during advanced age than at younger ages, and that the genetic effect in old age might be most pronounced for males. Such a difference between genders was recently suggested by Montesanto et al for Italians (Montesanto et al (2011)). …”
Section: Discussionsupporting
confidence: 60%
“…This hypothesis of stronger heritability of longevity among males was recently suggested by Italian researchers who studied 202 nonagenarians born around 1910 and their relatives in the province of Calabria, Italy (Montesanto et al 2011). The researchers found that brothers and sisters of male nonagenarians have better survival compared to siblings-in-law of male nonagenarians.…”
Section: Comparative Study Of Biological and Nonbiological Relativesmentioning
confidence: 72%
“…Numerous studies found that biological relatives of long-lived individuals have a substantial survival advantage compared to relatives of shorter-lived individuals (Pearl and Pearl 1934; Gavrilov and Gavrilova 2001b, 2014; Kerber et al 2001; Gavrilov et al 2002; Willcox et al 2006; Perls et al 2007; Smith et al 2009a), while relatively few studies analyze life span of nonbiological relatives (Schoenmaker et al 2006; Mazan and Gagnon 2007; Westendorp et al 2009; Montesanto et al 2011). At the same time, nonbiological relatives may serve as a nonbiased environmental control group in contrast to the general population control.…”
Section: Comparative Study Of Biological and Nonbiological Relativesmentioning
confidence: 99%
“…51 A sex-stratified self-contained setbased analysis of all SNPs investigated showed significance for both males and females (data not shown). Similarly, stratification of the competitive gene-set analysis yielded consistent significance of BER.…”
Section: Discussionmentioning
confidence: 96%